Pakistan’s potential trade and ‘behind the border’ constraints - Miankhel, Adil Khan (International Food Policy Research Institute, 2015)
Institutions are source of comparative advantage or disadvantage in international trade. Socio-economic and political constraints also matter for creating comparative advantage and affect the trade pattern of a country. These diverse ‘beyond the border’ and ‘behind the border’ constraints are often not fully captured in the literature on international trade and institutions. The existence of such institutional, socio-economic, and political constraints to Pakistani exports is empirically investigated in this paper through a cross-sec-tional analysis employing a trade Stochastic Frontier Gravity Model. Aggregate data for 2006-08 and 2009-11 show lower exports in the latter period. This is attributed to demand-suppressing effects emanating from the 2008 global financial crisis and supply-suppressing effects emanating from energy shortfalls and input constraints, due to floods, in Pakistan. The model estimation then demonstrates that behind the border con-straints in Pakistan are statistically significant in explaining total exports during 2009-11. The estimation is also presented for four single-digit SIC categories of products for this period. Behind the border constraints are evident for SIC 0 (agriculture, forestry and fish products) and SIC 2 (manufactured products) that com-bined account for approximately 80 percent of Pakistan’s exports. The estimation results by country further demonstrate that behind the border constraints affect the pattern of trade through the non-realization of bilateral trade potential. In the post-financial crisis era, Pakistan needs to further develop its institutional capacity to promote competitive exports given the explicit and implicit beyond the border trade barriers it faces and work to remove political obstacles to regional trade.